Research on the differences of RF port simulation and test of X-band power device package - Yan Huizeng; Shi Mengqiao; Zhou Hao; Chen Huanbei (Dianzi Jishu Yingyong, 2022)
This paper discussed research on the differences of RF Port simulation and test of X-band power device package which was based on probe test method. After optimizing it with simulation software, samples are produced through HTCC process line, the result of testing the port with GSG probe is much larger than the simulation results. It is analyzed by experimental methods such as control experiment and simulation result reproduction that the difference between S21 simulation and test is due to radiation loss, which affects the signal integrity of the signal in the return path. Insertion loss is greatly reduced after optimizing the structure, which proves that the radiation loss is the cause of the gap. Radiation loss can be effectively solved by electromagnetic shielding. This article can provide a reference for the design, test and practical use of high-power device packages.